Knowledge attitude and practice of breast feeding among women who delivered during COVID-19 pandemic in Kollam District, Kerala - R. S., Ammu; Janakiram, Chandra Sekar (International Journal Of Community Medicine And Public Health, 2023)
Background: Breastfeeding takes part a very important role in regulating and deciding the growth and development of the infant. However, its prevalence has remained low worldwide. Methods: A hospital-based cross-sectional study held in Taluk hospitals of Punalur and Karunagappally in Kollam district enrolled 100 mothers who had delivered from March 2020, attending the immunization center. purposive sampling was done and consent was obtained. The one-to-one interview was done with a pre-tested questionnaire to assess the knowledge, attitude, and practice on breastfeeding among mothers who delivered during the COVID-19 pandemic. Results: In the knowledge of respondents, 99% knew that colostrum is the first breast milk. 83% of respondents knew that colostrum is important for the baby to maintain immunity. The attitude of the mothers showed that 50% disagreed that formula feeding is more convenient than breastfeeding. 91% opined that breast milk is the ideal food. More than 90% said that breastfeeding is more convenient than formula. Conclusions: The level of exclusive breastfeeding is low among Indian mothers and the practice of breastfeeding is not as much as what is expected out of the high percentage of knowledge thus there is a need for improvement.